Pendampingan dan Penerapan Manajemen Strategi Untuk Meningkatkan Usaha Mikro Kecil Menengah Kelurahan Bengkong Indah Kota Batam - Mulyadi Mulyadi; Andi Fadlilah; Maizar Maizar; Khadijah Khadijah (I-Com: Indonesian Community Journal, 2024)
Problems often faced by small businesses include limited capital, lack of market access, less strategic location, lack of management knowledge, and low quality of products or services, Method by providing Mentors or consultants who are ready to help MSMEs overcome obstacles to business development, identification of problems (Management / application activities) and Coaching (Mentoring), Lectures and video screenings Motivation, Product introduction to better consumers quickly and effectively through content, helps MSMEs plan sustainable growth, including the development of growth strategies such as market expansion, product innovation, and business diversification to achieve optimal growth